Guarantees for Exercising and Protecting the Property Right of Internally Displaced Persons - Z. I. Knysh (Bulletin of Kharkiv National University of Internal Affairs)
The author has researched property relations of internally displaced persons, the peculiarities of which are determined by their legal status and the lack of sufficient legislative regulation to protect their property status. It has been emphasized that the realization of property rights occurs through the will and actions of the owner, which must fully comply with legal requirements, because the right of the owner to actions and the actions themselves – differ from each other. The difference between the content of a subjective right and its realization is, first of all, that the content of a subjective right covers only the possible behavior of an authorized person, and the realization of the right is a real, concrete action that leads to legal consequences. Therefore, the realization of property rights by internally displaced persons is absolute, i.e. absolute civil rights apply to an indefinite number of persons, except for the right of the owner.